Short Notations and Reflections on Pantayong Pananaw - Moralina, Aaron Rom O. (Archīum Ateneo, 2024)
This paper answers the question “What is Pantayong Pananaw?” through the subject of its study, its methods, its mode of communicating knowledge, and how it has served as a conscious effort of counteracting Western historiographic discourse. It also discusses the limitations and pitfalls of Pantayong Pananaw as well as its possible directions and trajectories.